The Climate-Smart Agriculture Regional Strategy (EASAC) for the Central American Integration System (SICA) enabled the scaling of climate-smart agriculture across the region through at least 250 transformations on policy, institutional, and financial dimensions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
A set of CGIAR innovations have contributed to the implementation and scaling of the Climate-Smart Agriculture Regional Strategy for the SICA region (EASAC), which is the Central American Integration System. The Central American Agricultural Council (CAC) oversees EASAC's implementation, this regional body gathers Ministries of Agriculture of eight countries in the region. Since 2017, the EASAC has enabled the scaling of climate-smart agriculture (CSA) across the region evidenced through at least 250 transformations on the policy, institutional, and financial dimensions.